Normal kinematics of the upper cervical spine during the Flexion-Rotation Test - In vivo measurements using magnetic resonance imaging - Takasaki, H.; Hall, Toby; Oshiro, S.; Kaneko, S.; Ikemoto, Y.; Jull, G. (2011)
The Flexion-Rotation Test (FRT) is proposed to assess mobility primarily at C1-C2. However, there is no in vivo measurement investigating the validity of the FRT. The purpose of this study was 1) to examine measurement reliability of segmental upper cervical movements using magnetic resonance imaging and 2) to investigate the content validity of the FRT. Nineteen asymptomatic female subjects (mean age: 22.2 years) were evaluated with a 0.2-T horizontally open MRI unit. The segmental rotation angles from Occiput-C1 to C3-C4 and the C4 vertebra were assessed with the head maximally rotated to both the right and the left in two conditions - neck in neutral and in flexion. Good reliability of the method of measurement was suggested by error considerations. A repeated measure ANOVA revealed an interaction between the two different neck starting positions and segment levels (P < 0.0001). Post-hoc analysis revealed that there were significant reductions in the flexed position (P < 0.0001) except for at Occiput-C1. While there was only a 16.3% reduction in rotation range at C1-C2, the reduction was 68.1% at C2-C3, 61.4% at C3-C4, and 76.9% at segments below C4, respectively, supporting the content validity of the FRT as a clinical measure of atlanto-axial mobility.